Re-park an interactive facility for solid waste management - Dy, Al Kenrick K. (2013)
In a study of World Bank, it stated that the Philippines, together which China and India are the countries which will face the greatest challenge in Waste Management by the year 2025. The problem cannot actually be solved through the active participation of the citizenry. The design aims to raise awareness through proper communication and education which will become a pillar essential in resolving issues of Solid Waste Management. The thesis aims to design an interactive technology Park which will help raise awareness, promote research and information dissemination in the field of solid waste management through the integration of ecologically adaptive strategies.